Crosstalk between autophagy and immune cell infiltration in the tumor microenvironment - Yang, Tiantian; Zhang, Yang; Chen, Junhang; Sun, Longhao (Frontiers in Medicine, 2023)
Autophagy is a conserved process for self-degradation and provides cells with a rescue mechanism to respond to circumstances such as stress and starvation. The role of autophagy in cancer is extremely complex and often paradoxical. Most of the related published studies on tumors are always focused on cancer cells. However, present studies gradually noticed the significance of autophagy in the tumor microenvironment. These studies demonstrate that autophagy and immunity work synergistically to affect tumor progression, indicating that autophagy could become a potential target for cancer immunotherapy. Therefore, it is crucial to clarify the correlation between autophagy and various tumor-infiltrating immune cells in the tumor microenvironment. The context-dependent role of autophagy is critical in the design of therapeutic strategies for cancer.